Breaking the PSYCHcle: Impact of Psychoeducation on the Attitudes Towards Mental Illness of Two Barangays in Bataan, Philippines - Turla, Von Hansen Jan; Fernando, Al-Jean; Macatangay, Priscilla Gilyanie; Bayhon, Ma. Ranissa; Corona, Alyssa Isabela; Soldevilla, Kyle Louie; Villazor, Jayvie (Journal of Interdisciplinary Perspectives, 2024)
In the Philippines, pervasive stigma surrounding mental health care presents a formidable obstacle to addressing psychological concerns. This study delves into the impact of psychoeducation on the attitudes toward mental illness within two barangays in Bataan. Employing a quasi-experimental approach, participants were divided into two groups: an experimental group (n=15) engaged in a comprehensive six-module psychoeducation program, and a control group (n=15) attending a single session. Utilizing the 21-item Community Attitudes Towards the Mentally Ill (CAMI) scale by Taylor and Dear for both pre- and post-intervention evaluations, the research revealed a significant enhancement in attitudes among participants from both experimental (p = 0.001) and control (p = 0.024) groups. Interestingly, the effect size was more pronounced in the control group (0.658 > 0.369), emphasizing the potent impact of psychoeducation. These findings underscore the transformative potential of psychoeducational initiatives in cultivating a more inclusive and empathetic community approach to mental health, advocating for their integration into comprehensive mental health strategies across the Philippines.